If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -56 + -4y = -28 Solving -56 + -4y = -28 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + -4y = -28 + 56 Combine like terms: -56 + 56 = 0 0 + -4y = -28 + 56 -4y = -28 + 56 Combine like terms: -28 + 56 = 28 -4y = 28 Divide each side by '-4'. y = -7 Simplifying y = -7
| 1x=32 | | -12x^2+12=0 | | 8+3x=-24 | | 2+y=5 | | 9x-18=-27 | | 4x^3+12x=0 | | 22+x=4-8x | | 4=3t-2 | | 4r^2+32r=0 | | 194-2x=43x+24 | | 3x-6=-99 | | -0.4x+3=1 | | -21=x-12 | | -21=x-13 | | -2(2s-3)-6=-2(4s+9)-2 | | 3+3y=-12 | | 82=-x+11 | | y=9-4 | | 2a-b=ac+3b | | 12=-6-x | | 8n+5n=65 | | y=2(4)-7 | | 14x+78-(32+12x)=134 | | 0.8w-0.4w+0.1w=2 | | y=2(3)-7 | | 62=15+x | | (3m-2)(m-2)=m(3m-8)+3m | | r+22=14 | | 51=-x+15 | | 3x+5y^15= | | 5x+4+6x+9=10x+5 | | 6x-(5x+5)=-1 |